Towards a sustainable Open Data Ecosystem: First steps for optimizing findability and user feedback - Aziz, Abdul; Herrera Murillo, Dagoberto Jose; Nogueras Iso, Javier; Lopez Pellicer, Francisco Javier (Jornada de Jóvenes Investigadores del I3A, 2022)
ODECO is a 4-year Horizon 2020 Marie Skłodowska-Curie Innovative Training Network initiative (grant agreement 955569) whose main aim is to train the next generation of creative and innovative early-stage open data researchers, to unlock their creative and innovative potential to address current and future challenges in the creation of user driven, circular and inclusive open data ecosystems. This paper describes the first steps performed for optimizing findability and user feedback.